What do the Angels Say? Alterity and the Ascents of Emanuel Swedenborg and the Baal Shem Tov - Esterson Rebecca (Open Theology, 2018)
This paper examines the history of boundary crossing and boundary preservation between Jews and Christians in the eighteenth century via an unorthodox path. Two men, a Swedish Lutheran natural philosopher and a charismatic Polish Rabbi, give their accounts of ascents to the heavens, both in the 1740s. The lives of Emanuel Swedenborg and the Baal Shem Tov did not intersect, but their otherworldly experiences tell related stories of strife between Jews and Christians while betraying something of a shared horizon concerning the future of their religious communities, and concerning sacred texts and their interpretation. Using a phenomenological framework informed by Emmanuel Levinas, and with theories of experience articulated by Steven Katz and Martin Jay at hand, this paper understands these accounts as articulations of relationship: not just the relationship between the subject and God, scripture, or the heavens, but articulations of the fraught relationship with the religious other in the earthly, human realm. By placing Swedenborg and the Besht, as it were, face to face, this paper emphasizes the presence of the religious other in their experiences, even in their private encounters with the Divine, and even though the intersubjectivity these experiences expose is characterized by difference, difficulty, and asymmetry.